One-Pot Telescoped Synthesis of Thiazole Derivatives from β-Keto Esters and Thioureas Promoted by Tribromoisocyanuric Acid - de Andrade, Vitor S. C.; de Mattos, Marcio C. S. (Synthesis, 2018)
A simple and efficient one-pot protocol has been developed for the synthesis of thiazole derivatives from readily available starting materials. Tribromoisocyanuric acid was successfully used for α-monohalogenation of β-keto esters in aqueous medium, which in the presence of thiourea and DABCO produced the corresponding 2-aminothiazoles in up to 87% yield. Extension of the reaction to thioacetamide and o-phenylenediamine led to 2-methylthiazole and quinoxalines, respectively. This approach enables telescoping of the two steps into a single process.
Keywords: heterocycles; condensation; thiazole; quinoxaline; green chemistry; tribromoisocyanuric acid; pot-ecomomy; thiourea